A study of yellow fever in Peru in relation to Ricardo Palma’s Tradiciones peruanas (Peruvian traditions) - Munayco Carhuamaca, Chris del Rosario (2023)
The traditions «Pepe Bandos» and «Cortar el revesino», by Ricardo Palma, narrate the appearance of yellow fever on the Peruvian coasts during the 18th century, as well as the infection that the Duke of Palata suffered from this viral disease when he arrived in Panama. This article will analyse both texts; the aim is to expose the origin of this epidemic, to develop a historical review of it and the impact it had on Peru.